Degradation of nickel utilizing phytoremediation with water lettuce and azolla microphylla - Harun, Hasnida; Mohd Redzwan, Nur Atiqah; A. Hamid, Hazren; Sunar, N.M.; Ahmad, Faridahanim; Ali, R.; Hamidon, Nuramidah; Mohamad, Mimi Suliza (Penerbit UTHM, 2020)
The ultimate disposal of wastewater can only be onto soil or into water. But whenever water courses are used for ultimate disposal, the wastewater is treated to prevent any injury to aquatic life in the receiving water. Diverse industrial wastes and anthropogenic activity have aggravated the problem of water pollution. This problem becomes complex because of the inorganic pollutants such as heavy metals that degrade easily and may hazardous when discharged into a water body.